6C.01: CULLIN-3 MUTATIONS LEADING TO SKIPPING OF EXON 9 ARE RESPONSIBLE FOR SEVERE CASES OF FAMILIAL HYPERKALAEMIC HYPERTENSION. (June 2015) - Picard, H. Louis Dit; Latreche, S.; Thurairajasingam, N.; Auzan, C.; Fiquet, B.; Frayssinet, R.; Garnier, A.; Jendruchova, V.; Lobbedez, T.; Martorell, L.; Mortier, G.; Pela, I.; et al.
Abstract : Objective: Familial hyperkalaemic hypertension (FHHt) also known as Gordon syndrome is a rare form of hypertension. Design and method: In 2001, WNK1 and WNK4, have been identified as responsible for this syndrome, regulating the ion transport in the kidney. In 2012, an American laboratory as well as ours, have identified two other genes, KLHL3 and CUL3 as responsible for the disease. These two unexpected genes are part of an E3-ubiquitin-ligase complex involved in the degradation of target proteins after ubiquitination, among them the WNK1 and WNK4 kinases. Results: We have identified 22 different mutations in KLHL3 in 27 index or familial cases. 19 are autosomal dominant, four recessive inheritance and four de novo mutations. There is a wide phenotypic variability, recessive cases have an earlier age at diagnosis, but blood pressure levels and similar serum K+ and Cl- levels. We have also identified seven missense mutations in the CUL3 gene in nine cases. All these mutations are located at the splice sites of exon 9, resulting in a loss in phase of 57 amino acids. Five cases have the mutations at a de novo state and two exhibit autosomal dominant proved. These patients are characterized by an earlier age of diagnosis and a severe phenotype. Patients with a CUL3 mutation have a stronger phenotype compared to other patients affected by other genes responsible for FHHt (WNK1, WNK4, KLHL3), suggesting other damages, vascular particularly. For some patients, a growth delay was observed, a possible consequence of the high metabolic acidosis and/or an effect of the mutation CUL3-delta-exon9 on the half-life of proteins involved in the development. Analysis by Bioluminescence Resonance Energy Transfer shows a direct interaction between KLHL3-CUL3-delta-exon9 stronger compared to the KLHL3-CUL3-wt. The CUL3-delta-exon9 mutation also causes an increase in the CUL3 neddylation, suggesting an increased ability to degrade its partners to the proteasome. Conclusions: In conclusion, there is a large phenotypic heterogeneity of FHHt, largely explained by genetic heterogeneity. CUL3-delta-exon9 mutations cause a severe disease in these patients, opening the way for additional research on the E3-ubiquitin-ligase complex CRL.